Syncope Protocols and Units Improve Diagnosis and Risk Stratification and Reduce Costs - Rizzo, Toni (MD Conference Express, 2015)
Newer syncope protocols can improve diagnostic accuracy and risk stratification in patients presenting with syncope, leading to more appropriate treatment and reduced recurrence rates and mortality. Adherence to syncope protocols also reduces hospital admissions, inappropriate testing, and costs of diagnosis and treatment.